2001
DOI: 10.1093/bja/87.6.912
|View full text |Cite
|
Sign up to set email alerts
|

The new neuromuscular blocking agents: do they offer any advantages?

Abstract: The pharmacodynamics and pharmacokinetics of the two most recent aminosteroid neuromuscular blocking drugs to become available, rapacuronium bromide (Org 9487) and rocuronium bromide are reviewed. Two new classes of drug with neuromuscular blocking properties, the bis-tetrahydroisoquinolinium chlorofumarates and the tropinyl diester derivatives are introduced. Comparisons between these drugs and mivacurium and cisatracurium are made. Rapacuronium 1.5 mg kg(-1) (ED95 1 mg kg(-1)), produces maximal neuromuscular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 108 publications
(105 reference statements)
0
23
0
2
Order By: Relevance
“…The use of prolonged infusions of rocuronium has been questioned recently because of the potential drug accumulation in patients with renal and/or hepatic failure [4]. Our data may provide another argument against this practice.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The use of prolonged infusions of rocuronium has been questioned recently because of the potential drug accumulation in patients with renal and/or hepatic failure [4]. Our data may provide another argument against this practice.…”
Section: Discussionmentioning
confidence: 75%
“…After diaphragm homogenization in KPO 4 buffer, equal amounts of protein were separated by SDS-polyacrylamide gel electrophoresis and transferred by semidry blotting. Blots were exposed to a monoclonal primary antibody to αII-spectrin (Biomol, PA).…”
Section: Calpain Activity and Calpastatin Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Показатели нервно-мышечной проводимости (Ме (25%-75%)) большинстве исследований, где изучалась без-опасность применения цисатракурия и атра-курия, было показано, что цисатракурий вы-зывает меньшее число побочных реакций и осложнений [9,10]. Однако в других работах достоверно значимых различий между дан-ными релаксантами выявлено не было [11].…”
Section: таблицаunclassified
“…[8][9][10][11] Sugammadex quickly inactivated rocuronium by encapsulation, reversing its neuromuscular blocking effects. A number of animal studies followed, which confirmed the effectiveness of sugammadex at reversing aminosteroid muscle relaxants (with the greatest effect on rocuronium followed by vecuronium and pancuronium).…”
Section: Safety and Efficacy Of Sugammadex For Neuromuscular Blockadementioning
confidence: 99%